The Advancement of Western Epistemology in Islamic Education - Rozali, M.; Lubis, Nurul Syahrani (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This article examines the development of Western Epistemology in the World of Islamic Education. The findings in this paper explain that: There are two conflicting methods in achieving knowledge, namely rational and empirical methods. Both are biased methods in Western epistemology. In fact, in real terms, both methods play an equal role in discovering knowledge. Therefore, science is now more empirical in nature, placing greater emphasis on experience, observation and research/experimental plus Descartes' ways of thinking. This combination of reason and empirical is called the scientific method. This method developed rapidly and colored Western or general epistemology.